Chemically Modified Sago Waste for Oil Absorption - Ngaini, Zainab; Wahi, Rafeah; Halimatulzahara, Dayang; Mohd Yusoff, Nur An-Nisaa' (UPM, 2014)
Oil pollution remains a serious concern especially in Malaysia. Many strategies have been employed to overcome oil pollution. In this research, sago waste material abundantly found in Sarawak was used and chemically modified into an oil adsorbent . Sago waste cellulosic residues were modified using fatty acid derivatives. The capability of the chemically modified sago waste to absorb oil from aqueous solution was studied and compared with the untreated sago waste. The modified sago waste showed higher hydrophobicity than the untreated sago waste, implying that it is less affinity for water and also an excellent affinity for oil. This chemically modified sago waste would be the most suitable for applications where engine oil (i.e., Shell Helix HX5) is to be removed from an aqueous environment. The modified sago waste selectively absorbs the oil and remains on the surface and is to be removed when the application is complete.